Creating the Empress Politics and Poetry in the Age of Catherine II - Proskurina, Vera (Ars Rossica, 2011)
"In Creating the Empress, Vera Proskurina examines the interaction between powerand poetry in creating the imperial image of Catherine the Great, providing a detailed analysis of a wide range of Russian literary works from this period, particularly the main Classical myths associated with Catherine (Amazon, Astraea, Pallas Athena, Felicitas, Fortune, etc.), as well as how these Classical subjects affirmed imperial ideology and the monarch's power. Each chapter of the book revolves around the major events of Catherine's reign (and some major literary works) that give a broadframework to discuss the evolution of important recurring motifs and images."